Explanatory model of cattle death by starvation in Manitoba: Forensic evaluation - Whiting, Terry L. (Canadian Veterinary Medical Association, 2012)
Cattle death by starvation is a persistent annual event in Manitoba. Herds with more than 10% overwinter death loss are usually identified in the late winter or early spring. Field and postmortem findings suggest that there is complete mobilization of fat followed by inability to maintain adequate thermoregulation and death by cardiac arrest. Carcasses show only mild evidence of muscle catabolism and are in excellent preservation if located prior to or around the time of spring thaw. A forensic diagnosis of death by starvation-induced exposure can be made with a high level of confidence when considering field data, whole carcass appearance, and postmortem evaluation of residual fat stores.